COMMUNITY-BASED TOURISM FOR NATURAL CONSERVATION IN POHSANTEN VILLAGE IN BALI - Mihai Voda; I Wayan Jendra; Made Ruki (Politeknik Negeri Bali, 2019)
This article discusses the role of tourism in conserving the natural environment in Pohsanten village, Jembrana regency, Bali province in Indonesia. It is developed based on review of publications, observation and direct participation during a community-based tourism (CBT) development and a trekking route development. The trekking to the waterfall is used as a main attraction by Pohsanten CBT. Mesehe waterfall trekking reinforces forest conservation as it is incorporated re-forestation; potentially creates additional work opportunities for locals, hence, a sustainable source of income; and tourism activities in the forest prevent illegal actions conducted in the forest that damage the environment. Thus, Mesehe waterfall trekking is an inclusive activity of conservation and business combined. It is expected that this article could enrich academic discourse on natural tourism and conservation, particularly involving CBT that use natural environment as attraction.